Different smoking processes with the special fuel rods: Impart a smoky aroma to Souchong black tea - Weisu Tian; Jiao Feng; Jinyuan Wang; Hongzheng Lin; Qianlian Chen; Jiayun Zhuang; Guanjun Pan; Jiake Zhao; Lirong Tang; Zhilong Hao (Food Chemistry: X)
The smoky scent is the most distinctive feature for Souchong black tea. To reduce the dependence on pinewood in the smoking process of Souchong black tea, it is crucial to find an effective alternative smoking material. Five black tea samples were prepared via using specially designed fuel rods as the smoking material in this study. Sensory analysis showed that DS (smoking at the drying stage) had the most favorable aroma, featuring a pleasant smoky aroma with floral and fruity notes. 69 volatile compounds were detected in five tested samples. Key volatiles such as β-caryophyllene, nerolidol, guaiacol, and α-terpineol, known for their woody or smoky aroma, were prominent in both DS and TS (the traditional Lapsang Souchong process) samples (OAV > 1, VIP > 1 and P < 0.05). However, DS exhibited significantly lower concentration of these volatiles than TS, giving it a more pleasant aroma. Additionally, phenylethyl alcohol and α-farnesene were characteristic volatiles in FS (smoking at the fermentation stage) and DS, imparting a sweet, mildly smoky aroma. Therefore, using these specialized fuel rods to smoking process at drying stage is an optimal method for processing Souchong black tea. These findings provide a theoretical foundation for stabilizing Souchong black tea quality, promoting green and low-carbon tea production methods.